(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
Discussing low-dimensional algebraic auto-morphism principles and looking at some new data to back them up are the goals of this study. These concepts have been revised to simplify computation for Leibniz algebra auto-morphism. The importance of these freshly published methods for determining auto-morphism is then illustrated by a number of fascinating findings and relevant examples.